Allocation of Resources to Cyanogenic Glucosides Does Not Incur a Growth Sacrifice in Sorghum bicolor (L.) Moench - Sohail, Muhammad N.; Blomstedt, Cecilia K.; Gleadow, Roslyn M. (Plants (Basel), 2020)
In plants, the production of secondary metabolites is considered to be at the expense of primary growth. Sorghum produces a cyanogenic glycoside (dhurrin) that is believed to act as its chemical defence. Studies have shown that acyanogenic plants are smaller in size compared to the wildtype. This study aimed to investigate whether the small plant size is due to delayed germination or due to the lack of dhurrin derived nitrogen. A novel plant system consisting of totally cyanide deficient class 1 (tcd1) and adult cyanide deficient 1 (acdc1) mutant lines was employed. The data for germination, plant height and developmental stage during seedling development and final plant reproductive fitness was recorded. The possible role of phytohormones in recovering the wildtype phenotype, especially in developmentally acyanogenic acdc1 line, was also investigated. The data on plant growth have shown that the lack of dhurrin is disadvantageous to growth, but only at the early developmental stage. The tcd1 plants also took longer to mature probably due to delayed flowering. None of the tested hormones were able to recover the wildtype phenotype. We conclude that the generation of dhurrin is advantageous for plant growth, especially at critical growth stages like germinating seed by providing a ready source of reduced nitrogen.